Clinical efficacy and safety evaluation of camrelizumab plus lenvatinib in adjuvant therapy after hepatocellular carcinoma surgery - Wang, Xudan; Cao, Weiwei; Qiu, Yan; Ji, Hongchen; Yuan, Juzheng; Wu, Weikang; Liu, Fuyuan; Feng, Liangyong; Ding, Rui; Li, Xiao; Tao, Kaishan (Frontiers in Oncology, 2023)
Objective To assess the efficacy and safety of camrelizumab plus different targeted drugs in adjuvant therapy after hepatocellular carcinoma (HCC) surgery. Patients and Methods This retrospective cohort study included HCC patients after undergoing postoperative adjuvant lenvatinib therapy failure who received intravenous camrelizumab 200 mg every 3 weeks (C group, n=97), or the camrelizumab plus oral apatinib 250 mg daily (C+A group, n=125), or the camrelizumab plus oral lenvatinib 12 mg daily (for bodyweight ≥60 kg)/ lenvatinib 8 mg daily (for bodyweight <60 kg) (C+L group, n=120), or the camrelizumab plus oral sorafenib 400 mg bi-daily (C+S group, n=114) between Oct 2020 and Oct 2021. The outcomes included objective response rate (ORR) and disease control rate (DCR) were evaluated by RECIST 1.1 and iRECIST. The median progression-free survival (mPFS), median overall survival (mOS), 6-months OS rate, 12-months, and adverse events were evaluated. Results As of May 31, 2022 with last follow-up time, the ORR was 17.2% for C group, 44.6% for C+A group, 47.9% for C+L group, and 36.3% for C+S group. The DCR was 72.0% for C group, 81.8% for C+A group, 85.5% for C+L group, and 77.9% for C+S group. The mPFS was 11.0 months (10.1-12.8) for C group, 14.0 months (12.7-16.5) for C+A group, 18.0 months (16.9-20.1) for C+L group, and 12.0 months (9.7-14.4) for C+S group. The mOS was 13.0 months (11.6-15.3) for C group, 17.0 months (15.8-19.4) for C+A group, 19.0 months (17.7-20.2) for C+L group, and 15.0 months (14.1-17.3) for C+S group. Grade 3 or 4 treatment-related adverse events occurred in 14 patients (14.4 %) for C group, 10 patients (8.0 %) for C+A group, 5 patient (4.2 %) for C+L group, and 11 patients (9.6 %) for C+S group. The most common adverse events were fatigue and transaminitis. Conclusions Camrelizumab combined with lenvatinib as adjuvant therapy showed promising efficacy and manageable safety in HCC patients. It might be a potential adjuvant therapy, or second-line treatment for patients with these patients.